The Hookah, an Emerging Form of Smoking, Systemic Effects and Harmful Effects of Its Use - Oliveira, Ellen Pierre; Assunção, Gabriela Lins Medeiros; Tavares, Marcos Soares; Carvalho, Carlos Roberto Ribeiro; Barbas, Carmen Silvia Valente (Medical Research Archives, 2022)
Hookah originates from India and in the last years spread around the world. The culture and the mystique behind this device promoted the use among the young population. Despite the thought that is the new safe way to smoke tobacco, recent studies showed that it can be more harmful than the cigarette, becoming a public health problem. Hookah increases airway reactivity and inflammation, causing an inflammation in the respiratory and cardiovascular system. The inhaled smoke contains chemicals agents that are toxic to the lung. As known in the literature the inhaled substance can lead to an acute eosinophilic pneumonia with a pulmonary interstitial infiltrate on radiological image. The degree of pulmonary involvement is varied and may cause a serious condition, requiring hospital admission and intensive care support. The treatment consists of ceasing the hookah use and the use of systemic corticosteroids. One important damage to the health is the infection disease like the tuberculosis transmission, cause by sharing the devise. In the cardiovascular system, the alterations were increasing the cardiac frequency and blood pressure in addition to causing inflammation in the endothelium of the vessel. Long-term studies are needed to correlate the use of this device with the risk of developing cancer.